Bioclimatic drivers of forage growth and cover in alpine rangelands - Wang, Li; Ma, Wenmei; Zhou, Dan; Chen, Qi; Liu, Lu; Li, Long (Frontiers in Ecology and Evolution, 2023)
Context Climate change and human activities have significant impacts on the Qinghai–Tibetan Plateau; the alpine ecosystem in this region has been degraded. A decline in forage yield reduces the livestock carrying capacity, but an unmitigated increase may lead to overfeeding and damage to vegetation. These changes have eventually led to grassland degradation and a series of ecological problems. Therefore, it is essential to examine bioclimatic factors that affect forage growth in grasslands. Objective To identify bioclimatic factors associated with forage growth and coverage in the Qinghai–Tibetan Plateau. Methods We examined how forage growth and coverage are affected by 35 bioclimatic indicators published in a global database (CMCC-BioClimInd). Results and conclusions We comprehensively considered the relationship between 35 indicators and forage yield and coverage and found that the combination of temperature and precipitation indicators had a very high correlation with yield and coverage. When we evaluated the relationship between each index and forage yield, forage yield was found to be significantly correlated with 16 bioclimatic indices. Forage yield was positively correlated with yearly positive precipitation (R2 = 0.49, p < 0.05), annual precipitation (R2 = 0.48, p < 0.05), and precipitation of driest quarter (R2 = 0.47, p < 0.05), and negatively correlated with temperature seasonality (R2 = 0.52, p < 0.05), precipitation seasonality (R2 = 0.39, p < 0.05), and simplified continentality index (R2 = 0.48). Forage coverage was significantly correlated with 15 bioclimatic indicators. It showed positive correlations with precipitation of driest quarter (R2 = 0.36, p < 0.05), precipitation of driest month (R2 = 0.33, p < 0.05), and annual precipitation (R2 = 0.31, p < 0.05), and negative correlations with temperature seasonality (R2 = 0.415, p < 0.05), annual temperature range, precipitation seasonality, and simplified continentality index (R2 = 0.37, p < 0.05). Significance We identified bioclimatic indicators that affect forage growth in the northeastern Qinghai–Tibetan Plateau, and explored the physiological and ecological mechanisms underlying forage growth. Our results provide a scientific basis for future forage management, early determination of livestock carrying capacity, rational management of animal husbandry practices, and ecological protection and restoration efforts.